Stories of students identified as at-risk: insights into student retention and support at a South African University - Sing, Nevensha (My University, 2015)
The perturbing phenomenon of wastage (revealed through incidences of unsatisfactory levels of student retention, poor pass and completion rates and an increase in repetition rates) is a course of concern for universities as it has a bearing on financial expenditure as well as institutional reputation. For the purpose of this study being at-risk is synonymous with being vulnerable.Student vulnerability is not a homogeneous phenomenon and therefore different student support structures, strategies and policies need to be devised for different issues and problems experienced by vulnerable students. This study argues that as long as effective and adequate institutional support is lacking, student vulnerability will continue to be a 'wastage' catalyst. [Abbreviated Abstract. Open document to view full version - Abstract would not load onto DSpace]
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: Dropouts--South Africa; Universities and colleges--South Africa; Education, Higher--South Africa--Evaluation; Minorities--Education--South Africa; Academic achievement--South Africa; Youth with social disabilities--Education--South Africa; Narrative inquiry (Research method)--South Africa